2001
DOI: 10.1152/jn.2001.85.5.2100
|View full text |Cite
|
Sign up to set email alerts
|

The Motor Output and Behavior Produced by Rhythmogenic Sacrocaudal Networks in Spinal Cords of Neonatal Rats

Abstract: The characteristics of the rhythmic motor output and behavior produced by intrinsic sacrocaudal networks were studied in isolated tail-spinal cord preparations of neonatal rats. An alternating left-right rhythm could be induced in the sacral cord by stimulus trains applied to sacrocaudal afferents at various intensities. Strengthening the stimulation intensity enhanced the rhythmic efferent firing and accelerated the rhythm by < or =30%. High stimulation intensities induced tonic excitation or inhibition and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 32 publications
0
32
0
Order By: Relevance
“…Recent clinical studies have shown that reactivation of the CPGs in spinal cord injury patients by afferent input is possible, and that it improves the motor function and mobility of patients with incomplete thoracic spinal injury (Wernig et al, 1995;Colombo et al, 2001;Dietz et al, 2002;Dietz and Harkema, 2004;Dietz, 2009). Our findings that stimulation of sacrocaudal afferents (SCAs) in the isolated spinal cord of the neonatal rat is a potent activator of the pattern generating circuitry in the sacral and limb moving segments Delvolvé et al, 2001;Strauss and Lev-Tov, 2003;Gabbay and Lev-Tov, 2004;Blivis et al, 2007; also see Whelan et al, 2000, for the neonatal mouse) enable us to use this preparation to study the functional organization and mechanism of action of the pathways that are involved in sensory-activation of the CPGs, under controlled in vitro conditions. Our previous work revealed that the SCA-induced rhythm is not generated by direct contacts between the stimulated afferents and the hindlimb CPGs, but that it involves synaptic activation of sacral neurons whose axons project to the hindlimb innervating segments of the spinal cord through the white matter funiculi (Strauss and Lev-Tov, 2003;Lev-Tov and O'Donovan, 2009;Lev-Tov et al, 2010).…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…Recent clinical studies have shown that reactivation of the CPGs in spinal cord injury patients by afferent input is possible, and that it improves the motor function and mobility of patients with incomplete thoracic spinal injury (Wernig et al, 1995;Colombo et al, 2001;Dietz et al, 2002;Dietz and Harkema, 2004;Dietz, 2009). Our findings that stimulation of sacrocaudal afferents (SCAs) in the isolated spinal cord of the neonatal rat is a potent activator of the pattern generating circuitry in the sacral and limb moving segments Delvolvé et al, 2001;Strauss and Lev-Tov, 2003;Gabbay and Lev-Tov, 2004;Blivis et al, 2007; also see Whelan et al, 2000, for the neonatal mouse) enable us to use this preparation to study the functional organization and mechanism of action of the pathways that are involved in sensory-activation of the CPGs, under controlled in vitro conditions. Our previous work revealed that the SCA-induced rhythm is not generated by direct contacts between the stimulated afferents and the hindlimb CPGs, but that it involves synaptic activation of sacral neurons whose axons project to the hindlimb innervating segments of the spinal cord through the white matter funiculi (Strauss and Lev-Tov, 2003;Lev-Tov and O'Donovan, 2009;Lev-Tov et al, 2010).…”
Section: Introductionmentioning
confidence: 56%
“…Rather, it involves several neural pathways which may act individually or as a group to initiate the rhythm. The mediating circuitry can be activated by perineal stimulation (Pearson and Rossignol, 1991), and by mechanical (Blivis et al, 2007) or irradiant heat stimulation of sacrocaudal dermatomes (Blivis et al, 2007;Mandadi et al, 2009), and by low-and high-intensity electrical stimulation of SCAs (Delvolvé et al, 2001;Blivis et al, 2007). Thus, the rhythm can be produced by activation of different sensory modalities and the nociceptive and nonnociceptive afferent pathways associated with them (Blivis et al, 2007;Mandadi et al, 2009).…”
mentioning
confidence: 99%
“…Spinal cord preparations (T6-Co3) were isolated from P3-P8 ether anesthetized rats (Delvolvé et al 2001;. The cord was transferred to a recording chamber and superfused continuously with an oxygenated artificial cerebrospi-nal fluid (ACSF; e.g., Delvolvé et al 2001;Kremer and Lev-Tov 1997;.…”
Section: Preparationsmentioning
confidence: 99%
“…The cord was transferred to a recording chamber and superfused continuously with an oxygenated artificial cerebrospi-nal fluid (ACSF; e.g., Delvolvé et al 2001;Kremer and Lev-Tov 1997;.…”
Section: Preparationsmentioning
confidence: 99%
“…Figure 1C indicates that, on the same preparation, the response induced by a rectangular pulse train (DRtrain) at 2 Hz (amplitude ϭ 1.5 Th) elicited a shorter episode of alternating oscillations, that lasted for 36.81 s, with only 13 cycles whose period and regularity (2.93 Ϯ 0.54 s and CV ϭ 0.19, respectively) were not different from those seen in response to FListim. Previous studies have demonstrated that even stronger DR square stimuli did not improve the length of FL (Atsuta et al 1990;Delvolvé et al 2001;Marchetti et al 2001a).…”
Section: Electrophysiological Recordingsmentioning
confidence: 86%